Аналіз впливу ефективності окремих відсіків потужної парової турбіни на результати оптимізації теплової схеми турбоблока - Усатий, Олександр Павлович; Жівотченко, Юлія В'ячеславівна (НТУ "ХПІ", 2018)
Стаття присвячена питанням оптимізації теплової схеми паротурбінної установки з використанням програмного комплексу DNA, створеного групою авторів Датського технічного університету та програмного комплексу багатопараметричної оптимізації, розробленого на кафедрі турбінобудування НТУ «ХПІ». Алгоритми оптимізації базуються на методах теорії планування експерименту (використовуються насичені плани Рехтшафнера) та методі створення формальних макромоделей цільових функцій підвищеної точності. Крім цього, для пошуку оптимальних рішень багатоекстремальних цільових функцій також були задіяні ЛПτ послідовності та метод пошуку оптимального рішення «Рій бджіл». По результатам розв’язання низки задач з оптимізації теплової схеми була проведена оцінка впливу ефективності окремих відсіків турбіни на значення параметрів, які оптимізуються. Залежно від постановки оптимізаційної задачі і обраного критерію якості були знайдені оптимальні варіанти теплової схеми турбоблоку, що забезпечують економію умовного палива від 10000 до 13000 т/рік. Також було виявлено факт істотного впливу рівня внутрішнього відносного ККД першого відсіку на оптимальний перерозподіл теплового перепаду турбіни між її відсіками.

This scientific paper is devoted to the optimization issues of the heat flow diagram of steam turbine plant. Optimal parameters of the heat flow diagram are searched for automatically by connecting the Dynamic Network Analysis (DNA) software system developed by the team of scientists from the Danish Technology University to the software system of multiparametric optimization developed by the Turbine Building Department of National Technical University "Kharkiv Polytechnic Institute". The applied optimization technique is based on the methods of experiment planning (saturated Rechtschafner plans are used), methods of improved accuracy and reliability of created formal macromodels of the finite function, the method of LPτ series and the method of "bee swarm" used for the search of optimal solution of multiextreme finite function. Based on the solution data of a number of the problems on the heat flow diagram optimization we evaluated the influence of the efficiency of individual turbine compartments on optimized parameter values. Depending on the formulation of optimization problem and selected quality criteria the optimal options for the heat flow diagram of the turbine plant were found that provide the saving of conventional fuel in amount of 10000 to 13000 t/year. In addition, the research done allowed us to define the most promising approaches to a further increase in the efficiency of heat flow diagrams of the turbine plant. A considerable influence of the level of internal relative coefficient of efficiency of the first compartment on optimal redistribution of the heat difference between the turbine compartments has been established.
Analyzing the influence of the efficiency of individual compartments of high-power steam turbine on the optimization data of a heat flow diagram of the turbine plant
Keywords: планування експерименту; критерії якості; DNA; heat flow diagram; quality criteria